2018
DOI: 10.1182/blood-2018-07-859769
|View full text |Cite
|
Sign up to set email alerts
|

Five-year follow-up of lenalidomide plus rituximab as initial treatment of mantle cell lymphoma

Abstract: We report 5-year follow-up of a multicenter phase 2 study of lenalidomide plus rituximab (LR) as initial treatment of mantle cell lymphoma (MCL). The regimen includes induction and maintenance with the LR doublet. Treatment was continuous until progression, with optional discontinuation after 3 years. The median age of the 38 participants was 65 years, with MCL international prognostic index scores balanced among low, intermediate, and high risk (34%, 34%, and 32%, respectively). Twenty-seven (75%) of the 36 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 42 publications
1
75
2
2
Order By: Relevance
“…Promising overall survival results were obtained from adding bortezomib to the R‐CHOP regimen compared to R‐CHOP alone in a randomized study, but an increase in hematologic toxicity was noted . Recently, a 5 year follow up study on the lenalidomide with rituximab combination was reported. It included induction and maintenance with lenalidomide and rituximab in 38 elderly patients, and the majority (75%) completed >3 years of treatment.…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
“…Promising overall survival results were obtained from adding bortezomib to the R‐CHOP regimen compared to R‐CHOP alone in a randomized study, but an increase in hematologic toxicity was noted . Recently, a 5 year follow up study on the lenalidomide with rituximab combination was reported. It included induction and maintenance with lenalidomide and rituximab in 38 elderly patients, and the majority (75%) completed >3 years of treatment.…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
“…20 Lenalidomide-based oral regimens for initial treatment of unfit patients with MCL can also be considered, if available. 21 In the relapsed setting, oral medications should be preferred, including ibrutinib 22 and lenalidomide, 23 if not HTCT 3120 1-8 Please cite this article in press as: Perini…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%
“…However, the response rates and PFS seen with the SCR regimen compare favourably with other less intensive induction regimens. For example, the CR rate with SCR was higher than that seen in prospective studies using BR (40%), R‐cladribine (52%), R‐CHOP (34–42%), and VR‐CAP (rituximab, cyclophosphamide, doxorubicin and prednisone plus bortezomib; 53%) (Kluin‐Nelemans et al , ; Robak et al , ; Chen et al , ; Le Gouill et al , ; Visco et al , ; Chang et al , ; Ruan et al , ; Tam et al , ). Furthermore, although MRD testing was only available for 14 responding patients, all were MRD‐negative after induction.…”
Section: Discussionmentioning
confidence: 95%